Characterisation of fibrinogen and fibrin proteolysis by the neutrophil membrane - Kirsch, Richard (Division of Immunology, 2018)
Recent studies have identified a novel 600 kDa neutrophil membrane associated protease which degrades fibrinogen, fibrin and C-reactive protein (CRP) during incubation of these ligands with phorbol 12-myristate 13-acetate (PMA, 5-10 ng/ml) stimulated neutrophils. This proteolysis is predominantly an extracellular event which occurs through a ligand dependent release of this protease from the neutrophil. Degradation products arising from this proteolysis not only become neutrophil associated but influence a number of important processes occurring in inflammation and coagulation. The aim of the present 'study was to purify and further characterize this protease and investigate the location of the neutrophil associated fibrinogen and fibrin degradation products. Whilst enzyme purification procedures were unsuccessful, several observations made during these attempts suggested that the neutrophil membrane associated proteolytic activity displayed similar characteristics to proteases of the azurophil granule. The proteolytic activity of the membrane was concluded from inhibitor profiles, zymography, and the apparent molecular mass values and hydrophobicity of the fibrinogen degradation products that it generated, to be the composite action of the azurophil granule proteases, human neutrophil elastase, cathepsin G and possibly proteinase 3. Electron microscopy analysis of PMA stimulated neutrophils incorporated within fibrin clots revealed morphological changes suggestive of neutrophil degranulation, and the proteolytic activity released by these cells was shown to be identical to that of azurophil granule proteases with respect to the apparent molecular mass values of the fibrin products that it generated. Immunoelectron microscopy revealed minimal internalization of fibrin like material during this process suggesting that neutrophil mediated fibrinolysis under these conditions is predominantly an extracellular event. Immunoelectron microscopy was used to localise fibrinogen degradation products previously reported to be associated with the neutrophil following incubation with fibrinogen. This revealed neutrophil associated fibrinogen products to be intracellular. Internalisation appears to be the result of pinocytosis which is stimulated in the presence of PMA. Although internalisation may be enhanced by an initial interaction of fibrinogen with the neutrophil membrane, a large proportion of uptake occurs via the fluid phase. Both intact and degraded forms of fibrinogen can associate with the neutrophil. Internalised material is rapidly degraded intracellularly into low molecular weight products which are partially released into the surrounding medium. This intracellular degradation, however, contributes minimally to the overall degradation of fibrinogen by neutrophils; the major pathway is extracellular. The demonstration in this· study, that the previously identified fibrinogen- fibrin- and CRP-degrading activity of the neutrophil membrane is due to azurophil granule proteases co-incides with numerous recent reports suggesting that membrane bound forms of these proteases, due to their ability to evade naturally occurring protease inhibitors, are the biologically relevant forms of these proteases. The membrane expression of azurophil granule proteases has recently been shown to be under the control of a variety of inflammatory mediators. Thus, neutrophil mediated degradation of fibrinogen, fibrin and CRP in vivo may be tightly controlled by the regulated expression of azurophil granule proteases on the neutrophil membrane.